CLIMATE CHANGE AND DISASTERS RISK REDUCTION OF EARTH QUAKE - Uffaq Shahid; Hamna Ahmed; Harris Waheed (International Journal of Contemporary Issues in Social Sciences, 2024)
Disasters are significant disruptions to a community’s operations that are more severe than what it can handle on its own. The exposure and vulnerability of a community can be affected by a number of factors, including natural, man-made, and technological hazards. Seismic events are devastating occurrences with a low probability but high impact. They could heighten the effects on the economy, infrastructure, and health, among other things. The gradients might result from an earthquake. Aside from fatalities and injuries resulting from building collapses, earthquakes also carry medical risks. Fire, contaminated water, and electrical outages. Regardless of the fact that our ability to predict them is still relatively limited, research generally suggests that the number of structures adhering to modern earthquake resistant criteria is the most important factor in reducing implosion. When planning individuals for disasters like earthquakes, which involves city planning (which incorporates its compactness), urban planning notions must be taken into consideration. The number of open spaces and their spatial arrangement are sufficient for safe evacuation shelters. An extensive system of roads is always available to provide suitable escape routes. Regardless of how well climate change predictions pan eliminated lowering the risk of current weather-related disasters will cut losses and start the necessary climate change adaptation steps. Scheduling for extreme weather events has additional advantages because it helps people be ready for a range of other emergencies. The present investigation will make an effort to examine and provide a comparative analysis of earthquakes that have occurred over the last ten years following the years-long study of the facts. According to the available previous information, earthquake-resistant design strategies and policy recommendations will be developed. Many other earthquake-proof construction features will be considered in an in-depth investigation material depending on the building’s location and intended use. This research will lead to the Earthquake Resistant housing in Pakistan in the form of Earthquake Design Strategies, Policy Recommendation with the help of data extracted and studied.